2013
DOI: 10.2174/1874325001307010366
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Shoulder Arthroplasty – A Literature Review

Abstract: Professor Grammont revolutionised shoulder surgery with his reverse shoulder arthroplasty design. Patients who had poor results from a conventional shoulder replacement because of cuff deficiency can now be treated effectively. Although designed for cuff tear arthropathy, indications continue to evolve and broaden. The initial results look very promising and the implant has gained much popularity over the years. The article provides an extensive literature review of the indications, results and complications f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 79 publications
1
8
0
1
Order By: Relevance
“…Of the latter, 33 were excluded. In 19 reporting on patients who had undergone RSA or TSA, there were no rheumatoid patients with RSA [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]; nine studies on patients who had had an RSA for various aetiologies included one or more rheumatoid patients, but no or insufficient information was provided on their outcomes [26][27][28][29][30][31][32][33][34]; three review articles on RSA in patients with various conditions gave very little information, contained in a short paragraph [35,36], or limited information [37], for the RA group; there were also two articles of general information on shoulder arthroplasty reporting no own case series [38,39]. Two additional studies reported enough pertinent and useful information on several [40] or many [41] RA patients undergoing RSA, but they were excluded because the mean follow-up was less than 36 months and the longest did not reach five years.…”
Section: Study Selectionmentioning
confidence: 99%
“…Of the latter, 33 were excluded. In 19 reporting on patients who had undergone RSA or TSA, there were no rheumatoid patients with RSA [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]; nine studies on patients who had had an RSA for various aetiologies included one or more rheumatoid patients, but no or insufficient information was provided on their outcomes [26][27][28][29][30][31][32][33][34]; three review articles on RSA in patients with various conditions gave very little information, contained in a short paragraph [35,36], or limited information [37], for the RA group; there were also two articles of general information on shoulder arthroplasty reporting no own case series [38,39]. Two additional studies reported enough pertinent and useful information on several [40] or many [41] RA patients undergoing RSA, but they were excluded because the mean follow-up was less than 36 months and the longest did not reach five years.…”
Section: Study Selectionmentioning
confidence: 99%
“…The potential problems with overload of the deltoid muscle and loosening of the glenosphere have been pointed out [ 38 ], and these problems certainly need further elucidation. Although several complications have been reported, the prostheses used in many of these studies are older RTSA designs, and the surgical indications mostly refer to patients going through revision surgery or rotator cuff defiencies [ 58 ]. In a short five years perspective RTSA may turn out to be a better and more predictable option than other prostetic replacements and ORIF, also in a health economic perspective [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Implant stability was confirmed by checking all directions. Excessive tension or difficult reduction may lead to insufficiency fracture of scapula, acromion, or humerus, along with axillary nerve palsy due to traction injury ; hence, care was taken (4,9). The commercially available Zimmer system provided a retentive liner with 65!…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…With increasing popularity of RTSA for CTA in the last decade, its applications has expanded to a variety of other conditions, including massive cuff tears without glenohumeral arthritis, threeor four-part fracture of proximal humerus, posttraumatic malunion, revision shoulder arthroplasty, tumor resection arthroplasty, osteoarthritis with large glenoid bony defects, chronic dislocation of the shoulder, rheumatoid arthritis, and post-infectious arthritis (3,(5)(6)(7)(8)(9). RTSA has been adopted in Europe since the 1980s, whereas it was approved by the US Food and Drug Administration in November 2003.…”
Section: Introductionmentioning
confidence: 99%